Spontaneous perception of numerosity in humans - Guido Marco Cicchini (Nature Portfolio, 2016)
Humans as well as many other species have the ability to perceive the number of items, numerosity, but the mechanism by which this is achieved is unclear. Here the authors provide strong evidence in support of a spontaneous perception of numerosity without reliance on density and area estimation.